Assessing stress tolerance of SUBI and DRO1 introgression lines under flooding and drought conditions at different growth stages - Soe, Ibrahim; Odama, Emmanuel; Tamu, Alex; Wani, Aquilino Lado Legge; Ookawa, Taiichiro; Ismail, Abdelbagi M.; Sakagami, Jun-Ichi (Tech Science Press, 2025)
Rice varieties tolerant to submergence regulate shoot elongation during short-term submergence by expressing the SUB1A gene. In contrast, the deep-rooted DRO1 is effectively expressed under drought conditions to enhance water and nutrient uptake. This study investigates the growth and yield of rice with both SUB1A and DRO1 in the background of IR64, under early-season flooding, and mid-season drought. The study used a randomized complete design with two factors: soil moisture treatments (submergence, drought, and their combination) and genotypes. The genotypes included IR64, and three near-isogenic lines (NILs): NIL-SUB1DRO1, NIL-SUB1, and NIL-DRO1. Complete submergence was imposed for 7 days on 14-day-old seedlings, while drought was imposed on control and submerged plants following a 21-day recovery period from submergence, using 42-day-old plants. Variables were measured before and after treatments (submergence and drought), and at harvest or grain maturity. The stresses negatively affected the genotypes. At harvest, IR64 and NIL-SUB1DRO1 under both stresses showed a significant reduction in tiller numbers, shoot dry weights, and yields compared to their control plants. IR64 exhibited a significant delay in reaching flowering under all stresses. The rice introgression lines showed significant improvements in tolerance to the stresses. The study showed no negative consequences of combining drought and submergence tolerance in rice.